Belize : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This IMF staff report on Belize's 2013 Article IV Consultation highlights economic developments and macroeconomic outlook. Macroeconomic developments in 2012 were underpinned by robust output growth but clouded by uncertainties surrounding the debt restructuring and growth prospects of major trading partners. New provisioning, and loan classification standards implemented by the central bank at end-2011 have resulted in declining nonperforming loans (NPLs) in the banking system and improving provisioning. NPLs remain high at 20 percent of total loans at end-2012, with heavy concentration in one domestic and some international banks. In compliance with the new prudential measures, banks have been required to write off bad loans within 3-5 years.